Development of Instructional Package Using Innovation-Based Learning Model in High Frequency Engineering for Enhancing Innovative Analytical Thinking Skill - Singkorn, Supanya; Klinbumrung, Kanyawit; Akatimagool, Somsak (Ratchaphruek Journal, 2025)
This research developed an instructional package in high-frequency engineering based on an innovation-based instructional approach using the DLAAP learning model. This research article aimed to: 1) Develop an instructional package using the innovation-based learning model in high-frequency engineering to enhance innovative analytical thinking skills for the undergraduate level; 2) Examine the effectiveness of the developed Instructional package; 3) Compare students’ learning achievement: 4) Study students’ innovative analytical thinking skills; and 5) Evaluate students’ satisfaction. The study employed a quasi-experimental research design using a one-group pretest-posttest design. The sample group consisted of 27 undergraduate students from those enrolled in the Bachelor of Science in Technical Education Program at Rajamangala University of Technology Phra Nakhon selected through cluster random sampling. The data were analyzed by t-test, and efficiency criteria based on the E1/E2 standard. The research results found that 1) the quality of the developed teaching set was at a high level, 2) the efficiency of the teaching package was 77.35/76.90, 3) the students had a significantly higher achievement after learning than before learning at a statistical level of .05, 4) the students have innovative analytical thinking skills with an average of 79.26 percent, and 5) the students had the highest level of satisfaction. Therefore, innovation-based instruction can effectively promote essential 21st-century skills among learners.